2002
DOI: 10.1177/0810219
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Properties of Strong and Non-rigid Calcium Phosphate Cement

Abstract: A calcium phosphate cement (CPC) sets to form hydroxyapatite and has been used in dental and craniofacial applications. However, when CPC was used in periodontal repair, tooth mobility resulted in the fracture and exfoliation of the brittle implants. The aim of this study was to develop CPC-chitosan lactate composites with higher strength and increased strain before failure. It was hypothesized that the incorporation of chitosan lactate would render CPC non-rigid with improved properties. Two-way ANOVA showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 23 publications
0
55
0
1
Order By: Relevance
“…Chitosan has been shown to strengthen and toughen CPC [42,43], resist the washout of CPC paste in physiological solution, and accelerate CPC setting [39]. Chitosan lactate (referred to as chitosan; VANSON, Redmond, WA) was mixed with water at chitosan/(chitosan +water) mass fractions of: 0%, 5%, 10%, and 15%, to form four CPC liquids.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan has been shown to strengthen and toughen CPC [42,43], resist the washout of CPC paste in physiological solution, and accelerate CPC setting [39]. Chitosan lactate (referred to as chitosan; VANSON, Redmond, WA) was mixed with water at chitosan/(chitosan +water) mass fractions of: 0%, 5%, 10%, and 15%, to form four CPC liquids.…”
Section: Methodsmentioning
confidence: 99%
“…The paste in the mold was set in a humidor with 100% relative humidity for 4 h at 37 °C. Then the specimens were demolded and immersed in a physiological solution (1.15 mmol/L Ca, 1.2 mmol/L P, 133 mmol/L NaCl, 50 mmol/L Hepes, buffered to 7.4 pH) at 37 °C for 20 h prior to testing [42]. …”
Section: Methodsmentioning
confidence: 99%
“…Degradation of the fiber over time could coincide with the ingrowth of bone and a gradual transfer of load from the biomaterial to the natural bone. Another method was the addition of a biopolymer chitosan 20,22. It was shown that the addition of chitosan and fibers together into CPC had a synergistic reinforcement effect in enhancing the fracture resistance of CPC 22…”
Section: Introductionmentioning
confidence: 99%
“…Similar to CPCs, improvement of the material and mechanical properties have been achieved by incorporating biocompatible and bioresorbable reinforcement additives such as Vicryl meshes [53] or chitosan. [54] …”
Section: Osteoconductive Bone Substitutes: Biologics As Scaffoldsmentioning
confidence: 99%